Making Mites Fertilizer in Hydroponic Plants as a Form of Community Empowerment in Creating a Healthy Environment in Cibitung Wetan Village - Hana Lestari; Ima Rahmawati; Iis Rudiansyah; Sri Ardianti; Fitri Desy Lestari (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2022)
This study aims to empower the people of Cibitung Wetan Village to recognize and make MiTel fertilizer independently and to find out the benefits of MiTel fertilizer applied to hydroponic plants. This research method uses a survey method, with data collection techniques using questionnaires and interviews. The subjects of this study were members of the Seroja KRL and the Kondang KRL. The results showed that 83% of the people were able to make and apply MiTel fertilizer to plants. This research also discovered that there are many benefits of Mitel Fertilizer applied to hydroponic plants, such as it can increase plant fertility, stronger plant stems, fresh green leaf color, and a nearly fast plant growth period. In addition, the results of this study indicate that MiTel Fertilizer can be used as an innovation in Cibitung Wetan Village by empowering the community. The sustainability of this research is to empower the community through the mass production of MiTel Fertilizer.